Barriers to Family Planning Among Women With Severe Mental Illness. Issue 2 (3rd April 2022) - Lawley, Megan E.; Cwiak, Carrie; Cordes, Sarah; Ward, Martha; Hall, Kelli Stidham
Abstract: The family planning experiences of women diagnosed with severe mental illness (SMI) have been understudied, despite increased risk for unintended pregnancy and barriers to accessing healthcare. We interviewed 17 English-speaking women aged 18 to 55 diagnosed with SMI who were receiving treatment at an outpatient mental health clinic to learn about their family planning experiences. Some major themes emerged: (1) pregnancy intention, decision-making, and coercion and (2) access and barriers to reproductive care. The results demonstrate an unmet need for family planning in women with SMI and how these needs could be addressed by a partnership between family planning and psychiatric providers.